The Impact of Green Banking Disclosure and Financial Performance on the Profitability of Banks in Indonesia - Meilya Afanti Putri; Wahyu Pramesti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to examine the effect of green banking policies, capital adequacy, non-performing loans, bank operational efficiency, and bank liquidity on profitability. This study uses a quantitative method. Panel data regression is employed to achieve the research objectives by collecting data from 2020–2023 on banking sector companies listed on the IDX (Indonesia Stock Exchange). The results of this study reveal that green banking policy and bank liquidity have no significant influence on profitability. On the other hand, capital adequacy, non-performing loans, and bank operational efficiency demonstrate a significant influence on profitability. To showcase the novelty of the research, this study uses different objects and time periods compared to previous research. Keywords: Green Banking, Financial Performance, Profitability.